Understanding the Influence of Property Stigma on Overhang in Selangor’s Real Estate Market - Binti Huri, Norulelin; Ahmad Baharum, Zarita; Ting, Kien Hwa; Ishak, Noor Farhana Akrisha (International Journal of Property Sciences (E-ISSN: 2229-8568), 2025)
This study examines the impact of various forms of property stigma: environmental, social, geographical, psychological, public, minimal, and physical, on property overhangs in Selangor. Property overhang, characterized by unsold properties despite completion, presents a significant challenge for developers and policymakers in rapidly urbanizing regions. The research utilizes Spearman's rank correlation analysis to explore the strength and direction of associations between these stigma types and the likelihood of unsold properties. Data were collected from 161 respondents, all potential property buyers, in Selangor, providing a diverse perspective on how stigma affects market outcomes. The results reveal statistically significant positive correlations between all forms of stigma and property overhang, with environmental stigma showing the strongest correlation (rs = 0.497, p < .001). These findings emphasize the complex, multi-dimensional nature of property stigma and its significant role in influencing buyer perceptions and the marketability of properties. The study highlights the need for real estate professionals and policymakers to address physical and non-physical stigma factors, such as environmental hazards or social perceptions, to reduce property overhang and improve the absorption of unsold properties in the market.